Development of Interactive Chemistry Activity Book on Hydrocarbon Topics - Nicholas Noel Ferdiansyah; Natalia Diyah Hapsari (Jurnal Penelitian Pendidikan IPA, 2025)
The research developed an interactive chemistry activity book on hydrocarbon topics using modified 4D (Define, Design, and Develop) model. Validation by six experts yielded material and media validity scores of 0.78 and 0.80, respectively. Practicality tests involving students of SMA Negeri 1 Kalasan obtained an average score of 92.2%, and an effectiveness of as achieved at 79%. Thus, the activity book is considered valid, practical, and effective for supporting chemistry learning.